A novel baculovirus-derived promoter with high activity in the baculovirus expression system - Martínez-Solís, María (PeerJ, 2016)
The baculovirus expression vector system (BEVS) has been widely used to produce a large number of recombinant proteins, and is becoming one of the most powerful, robust, and cost-effective systems for the production of eukaryotic proteins. Nevertheless, as in any other protein expression system, it is important to improve the production capabilities of this vector. The orf46 viral gene was identified among the most highly abundant sequences in the transcriptome of Spodoptera exigua larvae infected with its native baculovirus, the S. exigua multiple nucleopolyhedrovirus (SeMNPV). Different sequences upstream of the orf46 gene were cloned, and their promoter activities were tested by the expression of the GFP reporter gene using the Autographa californica nucleopolyhedrovirus (AcMNPV) vector system in different insect cell lines (Sf21, Se301, and Hi5) and in larvae from S. exigua and Trichoplusia ni. The strongest promoter activity was defined by a 120 nt sequence upstream of the ATG start codon for the orf46 gene. On average, GFP expression under this new promoter was more than two fold higher than the expression obtained with the standard polyhedrin (polh) promoter. Additionally, the orf46 promoter was also tested in combination with the polh promoter, revealing an additive effect over the polh promoter activity. In conclusion, this new characterized promoter represents an excellent alternative to the most commonly used baculovirus promoters for the efficient expression of recombinant proteins using the BEVS.